SINTESIS PATI JAGUNG TERFOSFORILASI MELALUI TEKNIK GELOMBANG MIKRO [Microwave-Assisted Synthesis of Phosphorylated Corn Starch] - Atep Dian Supardan; Suminar Setiati Achmadi; Tun Tedja Irawadi (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2014)
SINTESIS PATI JAGUNG TERFOSFORILASI MELALUI TEKNIK GELOMBANG MIKRO [Microwave-Assisted Synthesis of Phosphorylated Corn Starch] Atep Dian Supardan*, Suminar Setiati Achmadi dan Tun Tedja Irawadi Departemen Kimia, Fakultas Matematika dan Ilmu Pengetahuan Alam, Institut Pertanian Bogor, Bogor Diterima 28 Maret 2013 / Disetujui 24 Februari 2014ABSTRACT Phosphorylated starch is a type of modified starches which is mostly imported. Commonly, starch to be modified must contain more than 25% of amylose. This study aimed to synthesize phosphorylated starch and evaluate its potency as a heavy metal adsorbent. Corn starch was subjected to phosphorylation through microwave-assisted reaction with a mixture of sodium dihydrogen orthophosphate and disodium hydrogen phosphate. The experiment was designed to optimize the pH, microwave radiation power, and phosphorylation time. The results showed that the maximum phosphate subtitution degree was obtained at pH of 6, microwave radiation of 500 W, and a reaction time of 10 minutes. The degree of subtitution ranged from 0.567 to 0.787. The physicochemical properties of the product i.e. swelling capacity, solubility, water binding capacity, and paste clarity were significantly different than that of the unmodified corn starch. The infrared spectrum showed a high peak absorption at the wavelength of 1651 cm-1, indicating hydrogen bond formation of phosphoric group-water- phosphoric group. In the fingerprint area, there were two new absorption peaks at 1200 and 990 cm-1, which were assigned for the P=O and C-O-P vibrations, respectively. The phosphorylated corn starch adsorbed methylene blue up to 73.3% and mercury up to 73.6%, suggesting the prospect of the microwave-assisted synthetic phosphorylated corn starch as an effective adsorbent for heavy metals.